Anesthetic management of a patient with multiple drug allergies for total proctocolectomy and ileoanal pouch anastomosis under general anesthesia - Tosh, Pulak; Rajan, Sunil; Kumar, Lakshmi (Indian Journal of Case Reports, 2019)
Hypersensitivity reactions are major causes of concern in the perioperative setting and their incidence is highly reported nowadays. We report a case of 30-year-old female with proven allergy to multiple anesthetic drugs on intradermal drug allergy testing who underwent total proctocolectomy and ileoanal pouch anastomosis under general anesthesia.. This case concluded that anesthesia for patients with multiple drug allergy undergoing laparotomy can be safely conducted under general anesthesia with supplemental epidural analgesia. It may be safer to avoid muscle relaxants and careful monitoring with prompt management of any adverse events perioperatively, is prudent for a favorable outcome in these patients.